Influence Of Physical Work Environment, Work Discipline and Communication on Performance of Service Employees Investment and Integrated Services One Door of Labuhanbatu Regency - Siti Rama; Junita Lubis; Fauziah Hanum (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the influence of the physical work environment, work discipline and communicationon the performance of employees at the Office of Investment and One Stop Services in Labuhanbatu Regency. The population in this study were 50 people. The sampling technique used was saturated sampling, so the sample size in this study was 50 people. The data collection method used a questionnaire/questionnaire. The results of multiple linear regression analysis obtained the equation Y = 1.411 + 0.700X1 + 0.251X2 + 0.477X3. In the partial test (t test) the regression coefficient of the physical work environment variable (X1) obtained a t value of 3.273 > t table 2.012 which means that the physical work environment variable has a positive and significant effect on the employee performance variable with a significant value of 0.002 < 0.05. The regression coefficient of the work discipline variable (X2) obtained the t value of 2.120 > t table 2, 012 which means that the work discipline variable has a positive and significant effect on the employee performance variable with a significant value of 0.039 <0.05. The communication variable regression coefficient (X3) obtained the t-count value of 2.132 > t-table 2.012, which means that the communication variable has a positive and significant effect on the employee performance variable with a significant value of 0.038 <0.05. The results of the F test obtained the Fcount value of 31,629 > Ftable 2.81 with a significance value of 0.000 <0.05 so it can be concluded that the variables of the physical work environment, work discipline and communication simultaneously have a positive and significant effect on employee performance.